Pengaruh Komunikasi, Disiplin, Dan Motivasi Kerja Terhadap Kinerja Karyawan (Study Pada PT. Mitra Cipta Abadi Mulia) - Fatmasari Fatmasari; Muhammad Agus Salim; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of communication, discipline, and work motivation on the performance of employees of PT. Mitra Cipta Abadi Mulia. The type of research used in this research is quantitative with the method of distributing questionnaires. The sample in this study was 35 respondents and data management used the SPSS computer program. This study has met the requirements of the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The variables used in this study are employee performance variables (the dependent variable), while the independent variables are communication, discipline, and work motivation.The results of the analysis show that communication, discipline, and work motivation simultaneously influence employee performance. Partially communication has a significant positive effect on employee performance, partially discipline has an insignificant positive effect on employee performance, and partially motivation has an insignificant positive effect on employee performance at PT. Mitra Cipta Abadi Mulia. Keywords: Communication, Discipline, and Work Motivation on Employee Performance.